2021
DOI: 10.1007/s10895-021-02732-1
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Hydroxy-1-naphthaldehyde Schiff Base for Turn‐on Fluorescence Detection of Zn2+ Based on PET Mechanism

Abstract: Zinc ion is closely related to human health. Its content in human body is small, while the effect is large. However, it is not the more the better, must be in a scienti c balance. Therefore, it is signi cant to the rapid detection of Zn 2+ in the environment and organism. Herein, a uorescent probe based on 2-hydroxy-1-naphthalene formaldehyde and furan-2-carbohydrazide was conveniently synthesized via Schiff base reaction. And this probe has been successfully applied to the accurate and quantitative detection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It can be found that the ∆E is greatly reduced when CPBI 2 is complexed with Cu 2+ (Figure 8). This indicates that a stable metal complex has been formed, which is further proof of coordination between metal ions and polymers [70,71]. molecular orbital (HOMO) is mainly distributed on the side containing NH2 at the end of the polymer.…”
Section: Sensing Mechanism Of Cpbis For Metal Ionsmentioning
confidence: 72%
“…It can be found that the ∆E is greatly reduced when CPBI 2 is complexed with Cu 2+ (Figure 8). This indicates that a stable metal complex has been formed, which is further proof of coordination between metal ions and polymers [70,71]. molecular orbital (HOMO) is mainly distributed on the side containing NH2 at the end of the polymer.…”
Section: Sensing Mechanism Of Cpbis For Metal Ionsmentioning
confidence: 72%
“…The emission intensity increased from 423 nm to 545 nm, and the limit of detection was found to be 5.5 M. A turn-on fluorescence Schiff base probe 12 (Figure 4) based on 2-hydroxy-1-naphthylaldehyde was developed for the recognition of Zn 2+ ions in real water samples by Mu et al 58 The probe was analyzed by absorption spectroscopy and showed three absorption bands at 262, 325, and 362 nm. A gradual decrease in the absorbance band was observed with the addition of Zn 2+ in the solution.…”
Section: Review Synopenmentioning
confidence: 99%
“…Developed a turn-on fluorescence Schiff base probe 12 (Figure 4) based on 2-hydroxy-1naphthylaldehyde for the recognition of Zn 2+ ions in the real water samples by Mu et al [58] The probe was detected with the help of absorption spectroscopy. This probe shows three absorption bands at 262, 325 and 362 nm, respectively.…”
mentioning
confidence: 99%
“…3.1.9 Zn 2+ sensor [240][241][242][243][244] . Zinc is an essential trace element, involved in several important functions in the human body such as metabolism of RNA and DNA, cell apoptosis, reproduction, immune system function, protein metabolism, etc.…”
Section: Materials Advances Reviewmentioning
confidence: 99%